2021
DOI: 10.1002/ijgo.13517
|View full text |Cite
|
Sign up to set email alerts
|

Adherence rates to a prediction tool identifying women with an increased gestational diabetes risk: An implementation study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…There is still a debate, over which criteria are better [ 147 ]. Other researchers from the Netherlands using the IADPSG/WHO 2013 criteria diagnosed GDM in 8.2% of patients and in 13.2% of GDM high-risk patients [ 148 ]. In a single center cohort study from Utrecht de Wit et al confirmed an increase in GDM prevalence using the IADPSG/WHO 2013 criteria compared to the WHO 1999 strategy, at 32.4% vs. 19.3% [ 149 ].…”
Section: Europementioning
confidence: 99%
“…There is still a debate, over which criteria are better [ 147 ]. Other researchers from the Netherlands using the IADPSG/WHO 2013 criteria diagnosed GDM in 8.2% of patients and in 13.2% of GDM high-risk patients [ 148 ]. In a single center cohort study from Utrecht de Wit et al confirmed an increase in GDM prevalence using the IADPSG/WHO 2013 criteria compared to the WHO 1999 strategy, at 32.4% vs. 19.3% [ 149 ].…”
Section: Europementioning
confidence: 99%
“…A possibilidade de seleção de pacientes com maior probabilidade de diagnóstico de DMG pela glicemia de jejum mostra sua importância nos cenários onde o teste de sobrecarga não possui fácil acesso, destacando que sua execução, além de demandar do recurso e do agendamento prévio, necessita de intervalo de tempo de duas horas para a coleta das amostras que o compõe. Outro ponto, por vezes negligenciado, é o desconforto oriundo da ingestão dos 75 g de glicose, razão pela qual muitas vezes as gestantes não conseguem executá-lo 58 .…”
Section: Considerações Finaisunclassified